2009
DOI: 10.1111/j.1095-8649.2009.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Tethering induces increased stress artifacts in social fish species

Abstract: Behaviour of juvenile mulloway Argyrosomus japonicus were investigated under laboratory conditions to determine the efficacy of estimating predation mortality using tethering. The occurrence and duration of stressed behaviour was evaluated for individual A. japonicus that were hooked but untethered, hooked and tethered and unhooked and untethered (free swimming), both in schools and in isolation. Tethered and hooked treatments showed a significantly higher incidence and duration of stressed behaviour over cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Although the size of the acoustic tag in this study necessitated use of fish larger than those that are usually stocked (280 mm as opposed to 80 mm, Taylor & Piola 2008), these results are still relevant to informing stocking strategies as the biology and ecology of mulloway do not change substantially between these sizes (Gray & McDonall 1993;Taylor et al 2006a). In conjunction with previous research on diet (Taylor et al 2006a), key habitat preference (Taylor et al 2006b), prey dynamics (Taylor 2008), predatory impact (Taylor & Suthers 2008), release strategies ) and social dynamics (Pursche et al 2009), this study further improves our understanding of life histories and optimises stocking strategies for mulloway. By releasing at three spatially distinct sites within the river it has been shown that juvenile mulloway reside within the region about which they are released, although they demonstrate a preference for mid-river sites and intermediate salinities, similarly to wild con-specifics (Gray & McDonall 1993).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Although the size of the acoustic tag in this study necessitated use of fish larger than those that are usually stocked (280 mm as opposed to 80 mm, Taylor & Piola 2008), these results are still relevant to informing stocking strategies as the biology and ecology of mulloway do not change substantially between these sizes (Gray & McDonall 1993;Taylor et al 2006a). In conjunction with previous research on diet (Taylor et al 2006a), key habitat preference (Taylor et al 2006b), prey dynamics (Taylor 2008), predatory impact (Taylor & Suthers 2008), release strategies ) and social dynamics (Pursche et al 2009), this study further improves our understanding of life histories and optimises stocking strategies for mulloway. By releasing at three spatially distinct sites within the river it has been shown that juvenile mulloway reside within the region about which they are released, although they demonstrate a preference for mid-river sites and intermediate salinities, similarly to wild con-specifics (Gray & McDonall 1993).…”
Section: Discussionsupporting
confidence: 54%
“…) and social dynamics (Pursche et al . ), this study further improves our understanding of life histories and optimises stocking strategies for mulloway. By releasing at three spatially distinct sites within the river it has been shown that juvenile mulloway reside within the region about which they are released, although they demonstrate a preference for mid‐river sites and intermediate salinities, similarly to wild con‐specifics (Gray & McDonall ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As C . aggregata is a gregarious species (Eschmeyer et al , ), four individuals collected on the same day as the focal individual were placed in the experimental aquarium around each of the respirometry chambers to avoid isolation stress (Pursche et al , ). This was done for all trials.…”
Section: Methodsmentioning
confidence: 99%
“…That tethered prey are likely more vulnerable to predation than untethered free-swimming prey is widely recognised, and most authors acknowledge this by interpreting their results as estimates of relative predation pressure rather than absolute predation rates (Aronson, 1989). Restraining mobile prey on a tether may alter its behaviour and thereby alter the probability of detection or consumption by predators relative to naturally behaving un-tethered prey (Aronson, 1989;Zimmer-Faust et al, 1994;Halpin, 2000;Pursche et al, 2009). The usual assumption in field tethering studies, as articulated by Peterson and Black (1994), is that if experimental methods are applied identically across all treatments, then any artefacts of this intervention will also be equal among treatments, and thus not bias the observed patterns.…”
Section: Introductionmentioning
confidence: 99%